2013
DOI: 10.7317/pk.2013.37.6.794
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Novel Temperature and pH Sensitive (NIPAM-co-MAA) Polymer Microgels and Their Volume Phase Change with Various Salts

Abstract: Novel microgels of N-isopropylacrylamide (NIPAM)-co-methacrylic acid (MAA) (NIPAM-co-MAA) with different contents of N,N-methylene bis acrylamide (MBA) were prepared by emulsion polymerization technique and were studied by Fourier transform infrared spectroscopy (FTIR), dynamic light scattering (DLS) and zeta potential measurement. Effect of pH, temperature and different salts concentration on the microgel particles was investigated. DLS results have shown that the hydrodynamic radius of the microgel increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
1
3
0
1
Order By: Relevance
“…Microgels with a lower degree of cross-linking (higher number of segments per chain) display greater swelling. This behavior of P­(NIPAm-MAA) microgels has been experimentally confirmed . Qualitatively, the response to salt concentration and pH is similar (panels B and C of Figure , respectively) for all chain lengths considered.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Microgels with a lower degree of cross-linking (higher number of segments per chain) display greater swelling. This behavior of P­(NIPAm-MAA) microgels has been experimentally confirmed . Qualitatively, the response to salt concentration and pH is similar (panels B and C of Figure , respectively) for all chain lengths considered.…”
Section: Resultssupporting
confidence: 66%
“…This behavior of P(NIPAm-MAA) microgels has been experimentally confirmed. 76 Qualitatively, the response to salt concentration and pH is similar (panels B and C of Figure 9, respectively) for all chain lengths considered. An interesting observation is that decreasing the cross-linking degree leads to a more sharp volume transition when the temperature increases (Figure 9A); in addition, T PT increases.…”
Section: Resultsmentioning
confidence: 75%
“…Meanwhile, Fig. 2c revealed the spectrum of P(NIPAM-co-AA), accordingly, its characteristic peak at around 1728 cm -1 was attributed to C=O stretching vibration in carboxylic acid group 8 , while other three feature bands at 1650 cm -1 , 1544 cm -1 and 1461 cm -1 were ascribed to C=O stretching vibration (amid I band), -NH bending(amid II band) and -C-N stretching vibration of acid amide group, respectively [16][17] . Additionally, the typical band of isopropyl group (CH-(CH 3 ) 2 ) at 1363 cm -1 and 2969 cm -1 corresponded to the -CH and -CH 3 stretching vibration 18 .…”
Section: Initiationmentioning
confidence: 99%
“…Karg et al, 7 explored the swelling behavior of PNIAM-co-Poly (AAA) at pH 8.0 and pH 10.0 with different incorporated allylacetic acid amounts. Recently, Khan et al, 8 and Chen et al, 9 found that the LCST of P(NIPAM-co-AA) became broaden and shifted to higher temperature range after incorporation of a small amount of carboxyl ionizable group into PNIPAM chains. Shibayam et al, 10 also concluded that the influence of the pH values and salt concentrations on their volume phase transition temperature was remarkable.…”
Section: Introductionmentioning
confidence: 99%
“…Los microgeles con menor grado de entrecruzamiento (mayor número de segmentos por cadena) presentan un mayor grado de hinchamiento, a iguales condiciones este comportamiento de los microgeles P(NIPAm-MAA) ha sido confirmado experimentalmente [172]. Cualitativamente, la respuesta a la concentración de sal y al pH es similar para todas las longitudes de cadena consideradas (paneles B y C de la figura 3.10, respectivamente).…”
Section: Efecto Del Grado De Entrecruzamientounclassified